Rockburst prediction and early warning for a highway tunnel excavated by TBM based on microseismic monitoring - Zhao, Jian; Huang, Dan; Cai, Yongshun; Huang, Dengxia; Zhou, Xiaolong; Wang, Fei; Pan, Yuxiang (Frontiers in Earth Science, 2024)
A newly developed microseismic (MS) monitoring system was employed in the Tianshan-Shengli tunnel to detect MS activities, and then to predict and early warn rockburst disasters. The system not only has the advantages of accuracy of artificial analysis, but also real-time analysis and warning of cloud service platform, of which positioning accuracy for MS events is about 5 ~ 10 m. And a new installation scheme of sensors was proposed to achieve the fast installation and recovery of sensors, taking advantage of semicircular steel tube and hose clamp. What's more, the rockburst risk level prediction criterion adopted multiple evaluation indexes such as MS event energy, moment magnitude and number, and it revealed that the evolution of maximum energy has a good positive correlation with that of maximum moment magnitude, through analyzing the monitored MS events. It also showed that the rockburst generally occurs after two days after the rockmass exposed from the tunnel boring machine (TBM) tail shield, belonging to delayed rockburst, according to the field statistical results of rockburst information. The preliminary application cases indicated that the rockburst prediction and early warning achievements based on MS monitoring have a good agreement with the site survey results. Therefore, the new MS monitoring system is a reliable tool to predict and early warn rockburst disasters.